Methyl ketone production by Pseudomonas putida is enhanced by plant‐derived amino acids. Issue 8 (29th April 2019) - Dong, Jie; Chen, Yan; Benites, Veronica Teixeira; Baidoo, Edward E.K.; Petzold, Christopher J.; Beller, Harry R.; Eudes, Aymerick; Scheller, Henrik V.; Adams, Paul D.; Mukhopadhyay, Aindrila; Simmons, Blake A.; Singer, Steven W.
Abstract: Plants are an attractive sourceof renewable carbon for conversion to biofuels and bio‐based chemicals. Conversion strategies often use a fraction of the biomass, focusing on sugars from cellulose and hemicellulose. Strategies that use plant components, such as aromatics and amino acids, may improve the efficiency of biomass conversion. Pseudomonas putida is a promising host for its ability to metabolize a wide variety of organic compounds. P. putida was engineered to produce methyl ketones, which are promising diesel blendstocks and potential platform chemicals, from glucose and lignin‐related aromatics. Unexpectedly, P. putida methyl ketone production using Arabidopsis thaliana hydrolysates was enhanced 2–5‐fold compared with sugar controls derived from engineered plants that overproduce lignin‐related aromatics. This enhancement was more pronounced (~seven‐fold increase) with hydrolysates from nonengineered switchgrass. Proteomic analysis of the methyl ketone‐producing P. putida suggested that plant‐derived amino acids may be the source of this enhancement. Mass spectrometry‐based measurements of plant‐derived amino acids demonstrated a high correlation between methyl ketone production and amino acid concentration in plant hydrolysates. Amendment of glucose‐containing minimal media with a defined mixture of amino acids similar to those found in the hydrolysates studied led to a nine‐fold increase in methyl ketone titer (1.1 g/L). Abstract : Plants are an attractive source of renewable carbon for conversion to biofuels and bio‐based chemicals. Conversion strategies often use a fraction of the biomass, focusing on sugars from cellulose and hemicellulose. Strategies that use plant components, such as aromatics and amino acids, may improve the efficiency of biomass conversion. Here we demonstrate that plant‐derived amino acids contribute to substantial increases in the production of methyl ketones, a potential diesel blendstock, by Pseudomonas putida.